Spanish Translation, Face Validity, and Reliability of the ICIQ-B Questionnaire with Colorectal Cancer Patients - Sacomori, Cinara; Lorca, Luz Alejandra; Martinez-Mardones, Mónica; Benavente, Paulina; Plasser, Jorge; Pardoe, Megan (Journal of Coloproctology, 2021)
Purpose To describe the English-to-Spanish translation process and preliminary psychometric analysis (face validity, cultural adaptation, and test-retest reliability) of the International Consultation on Incontinence Questionnaire – Bowels Module (ICIQ-B) among Chilean colorectal cancer patients.Materials and Methods The face validity was studied with 10 colorectal cancer patients, and the test-retest reliability, with 15 patients, 1 month before and 6 months after cancer surgery.Results Two rounds of translation/back translation resulted in a Spanish version. The English expression open your bowels was translated as defecar, as it is easily understandable in Spanish. The patients reported that the instrument was easy to answer, with clear instructions, and that it was adequate to appraise their health condition. The test-retest reliability was good (Spearman rho [ρ] ≥ 0.842); only item 15a, the Bristol Stool Scale, obtained a moderate correlation (ρ = 0.639). The patients reported a variety of symptoms, including increased bowel movements, nocturnal bowel movements, fecal urgency, and incontinence.Conclusions The first Spanish version of the ICIQ-B was culturally adapted for Chilean colorectal cancer patients, and showed good test-retest reliability. It might be a reference for other Spanish-speaking countries and for patients with other conditions. The ICIQ-B is a robust comprehensive questionnaire for bowel function.
Keywords: bowel function; fecal incontinence; colorectal neoplasms; validation study; surveys and questionnaires